Relapse and retention after orthodontic treatment - E., Elih (Padjadjaran Journal of Dentistry, 2015)
Orthodontic treatment results are potentially unstable that has a tendency to return to the former position. This is the so called relapses and therefore retention is necessary because the gingival and periodontal tissues are affected by orthodontic tooth movement and required time for reorganization when the appliances are removed. Retention is the prolonged dental detention that is done at the end of an orthodontic treatment with use of appliances designed for dental stabilization. The purpose of this paper is to explain the cause of relapse and a wide range to prevent relapse. The method used is based on literature. The conclusion is stabilizing treatment results with the retention procedure is an important part in orthodontic treatment. The patient must be given information about the implications of relapse and how to use the retainer, so that the patient can take responsibility for retention phase of treatment.